House Season 4 Disc 3 - Laurie, Hugh, 1959-; Edelstein, Lisa, 1967-; Epps, Omar.; Leonard, Robert Sean, 1969-; Morrison, Jennifer, 1979-; Spencer, Jesse, 1979-; Penn, Kal, 1977-; Jacobson, Peter; Wilde, Olivia; Shore, David, 1960-; Universal Pictures (Firm); Universal Studios Home Entertainment (Firm) (Universal City, CA : Universal Studios Home Entertainment, 2008)
Reunite with the perplexing and prickly Dr. Gregory House as he tackles impossible cases while putting a new staff of potential team members through the medical wringer with his trademark sarcasm and irreverent bedside manner.
Frozen -- Don't ever change -- No more Mr. Nice Guy -- Living the dream.
Title from container and disc label.
Created by David Shore.
Set contains all 16 episodes from the fourth season.
Hugh Laurie, Lisa Edelstein, Omar Epps, Robert Sean Leonard, Jennifer Morrison, Jesse Spencer, Kal Penn, Peter Jacobson, Olivia Wilde.
Originally broadcast on Fox during the 2007-2008 season.
Not rated.
Keywords: Physicians -- United States -- Drama; Physician and patient -- United States -- Drama; Medicine -- Specialties and specialists -- United States -- Drama; Hospitals -- Medical staff -- United States -- Drama; Medical care -- Needs assessment -- United States -- Drama; United States; Medical television programs (Drama); Drama; Fiction television programs; Medical television programs; Television programs for the hearing impaired; Television series; Medical drama (Television programs); Television serials